FORMULASI DAN UJI STABILITAS SEDIAAN LOTIONEKSTRAK BUAH JAMBU BIJI (Psidium guajava L.) SEBAGAI PELEMBAB KULIT - Yanti, Silfera Indra; Oktaviani, Ade Wulan; Irwanto, Moh. Firman (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Lotion from guava fruit can be used because it is efficacious as a moisturizer and antioxidant and has the potential to produce products that can be used in real life. Objective to formulate guava fruit extract in the manufacture of lotion preparations, to assess what is the moisture content is, determine what are the physical and medicinal requirements of guava fruit extract (Psidium guajava L.) and measure the stability of the formulated lotion preparation. Using an experimental method to determine the formulation and stability test of guava fruit extract lotion preparations (Psidium guajava L.) as a skin moisturizer. Results is guava fruit was formulated into a lotion preparation with the formulas F1 (15%), F2 (20%), and F3 (25%). The moisture values of all preparations increased during the 3 days of inspection. However, in each evaluation result, the most stable and good for lotion preparations is at F3 (25%) because the higher the concentration, the better it is for moisturizing the skin and stable for lotion preparations. Guava fruit extract lotion has met the evaluation parameters. All preparations are stable in storage for 21 days at room temperature 28°C and all preparations do not irritate the skin. Conclusion guava fruit extract can be formulated into a lotion preparation, proven to have ingredients to moisturize the skin and has good physical and chemical characteristics of drug stability